Smart board Z8 encore based message board - Cortezano, Fianile J. (2005)
Text messaging is a technology frequently used in the country. The Philippines is now known as the Texting Capital of the World. With this knowledge, text messaging should be utilized to create other technologies that can take advantage of its use. One example of these, is using text messaging in electronic or LED billboards. This is what the smart board system does. Nowadays, electronic billboards are getting popular specially in the advertising industry. Electronic billboards has many advantages. It saves money, targets correct market better, saves time in putting up, is animated and more visible, can be placed in any location, and has flexible contracts. Using the smart board system will make it faster in putting up advertisements. It only takes a few seconds before a text message arrives at its destination so it can be displayed immediately. It will make contracts more flexible since after displaying a message, it automatically deletes it so if one wants more messages displayed, one simply needs to text again. Also, it makes the system interactive. A person only needs to know the number of the smart board, as well as the character codes for his or her message to be displayed. The Internet is also widely used nowadays. Instead of texting messages for display, a webpage can be made to submit messages to a webserver. The webserver has a connected GSM unit to its serial port that can send the message to the message board for display. These advantages makes the system ideal for advertisements, putting up announcements or simply displaying messages.
Thesis (B.S. E.C.E.)--University of the Philippines Diliman.
Keywords: Zilog Z-80 (Microprocessor); Computer bulletin boards; Z8 Encore; Smartboard